Designer patterned functional fibers via direct imprinting in thermal drawing - Wang, Zhe (2022)
Creating micro/nanostructures on fibers is beneficial for extending the application range of fiber-based devices. To achieve this using thermal fiber drawing is particularly important for the mass production of longitudinally uniform fibers up to tens of kilometers. However, the current thermal fiber drawing technique can only fabricate one-directional micro/nano-grooves longitudinally due to structure elongation and polymer reflow. Here, we develop a direct imprinting thermal drawing (DITD) technique to achieve arbitrarily designed surface patterns on entire fiber surfaces with high resolution in all directions. Such a thermal imprinting process is simulated and confirmed experimentally. Key process parameters are further examined, showing a process feature size as small as tens of nanometers. Furthermore, nanopatterns are fabricated on fibers as plasmonic metasurfaces, and double-sided patterned fibers are produced to construct self-powered wearable touch sensing fabric, revealing the bright future of the DITD technology in multifunctional fiber-based devices, wearable electronics, and smart textiles.